2020
DOI: 10.1002/jsfa.10850
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of enzymes associated with metabolic and neurological disorder by dried pomegranate sheets as a function of pomegranate cultivar and fruit puree

Abstract: BACKGROUND Obesity and type 2 diabetes mellitus are the most extended current chronic diseases and also Alzheimer pathology which is a progressive degenerative neurological disorder. Therefore, finding effective enzyme inhibitors responsible for the development of these diseases are essential. Therefore, the aim of this study was to investigate the impact of fruit purée (Cydonia oblonga, Ziziphus jujube and Malus domestica) and pomegranate juice cultivar (‘Mollar de Elche’ and ‘Wonderful’) of dried pomegranate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Moreover, PG inhibits the dipeptidyl peptidase-4 enzyme that is linked to glucose metabolism by degrading the incretin hormones glucagon-like peptide-1 and glucosedependent insulinotropic polypeptide, thereby stimulating insulin secretion [159]. Furthermore, PG exhibited powerful activity in reducing glucose absorption via the inhibition of pancreatic lipase and α-amylase enzyme activities responsible for the digestion of fat and carbohydrates, respectively [160]. It was reported that PG can establish its hypoglycemic influence via inhibition of cytochrome P450 (CYP)2C9 that is responsible for the metabolization of some hypoglycemic sulfonylureas such as tolbutamide, thus increasing the efficacy of hypoglycemic drugs [161].…”
Section: Punica Granatum (Pg)mentioning
confidence: 99%
“…Moreover, PG inhibits the dipeptidyl peptidase-4 enzyme that is linked to glucose metabolism by degrading the incretin hormones glucagon-like peptide-1 and glucosedependent insulinotropic polypeptide, thereby stimulating insulin secretion [159]. Furthermore, PG exhibited powerful activity in reducing glucose absorption via the inhibition of pancreatic lipase and α-amylase enzyme activities responsible for the digestion of fat and carbohydrates, respectively [160]. It was reported that PG can establish its hypoglycemic influence via inhibition of cytochrome P450 (CYP)2C9 that is responsible for the metabolization of some hypoglycemic sulfonylureas such as tolbutamide, thus increasing the efficacy of hypoglycemic drugs [161].…”
Section: Punica Granatum (Pg)mentioning
confidence: 99%